Functional electrical stimulation following nerve injury in a large animal model. Issue 6 (25th March 2019) - Cercone, Marta; Jarvis, Jonathan C.; Ducharme, Norm G.; Perkins, Justin; Piercy, Richard J.; Willand, Michael P.; Mitchell, Lisa M.; Sledziona, Michael; Soderholm, Leo; Cheetham, Jonathan
ABSTRACT: Introduction : Controversy exists over the effects of functional electrical stimulation (FES) on reinnervation. We hypothesized that intramuscular FES would not delay reinnervation after recurrent laryngeal nerve (RLn) axonotmesis. Methods : RLn cryo‐injury and electrode implantation in ipsilateral posterior cricoarytenoid muscle (PCA) were performed in horses. PCA was stimulated for 20 weeks in eight animals; seven served as controls. Reinnervation was monitored through muscle response to hypercapnia, electrical stimulation and exercise. Ultimately, muscle fiber type proportions and minimum fiber diameters, and RLn axon number and degree of myelination were determined. Results : Laryngeal function returned to normal in both groups within 22 weeks. FES improved muscle strength and geometry, and induced increased type I:II fiber proportion (p = 0.038) in the stimulated PCA. FES showed no deleterious effects on reinnervation. Discussion : Intramuscular electrical stimulation did not delay PCA reinnervation after axonotmesis. FES can represent a supportive treatment to promote laryngeal functional recovery after RLn injury. Muscle Nerve 59:717–725, 2019